THE CONCEPT OF MAQASID ASYSYARIAH IN MALAYSIA’S FOREIGN POLICY ON PALESTINE FROM 1957-2003 - MOHD SALLEH, MOHAMAD RIDHAUDDIN (2017)
The discussion about the role of maqasid asy-syariah in Malaysia’s foreign policy is yet widely being discussed among scholars. Therefore, the objectives of this study is to examine the development of Malaysia’s foreign policy on Palestine from 1957-2003 and to analyse Malaysia’s foreign policy based on maqasid asy-syariah perspective. This study has discussed about the theoretical framework of maqasid asy-syariah and Malaysia’s foreign policy which was discussed in the second and the third chapter. This study also explaining about the actual foreign policy on Palestine which was being practiced by Malaysia during 46 years after independent in the fourth chapter. Whereas in the fifth and sixth chapter I have tried to suggest my analysis of Malaysia’s foreign policy on Palestine from 1957-2003 based on Maqasid asysyariah perspective, explaining about the implication of this study to Malaysian Government as well as to the knowledge and suggesting road to be taken for further research.